Learning styles among students in learning Arabic at Darussalam Modern Islamic Boarding School Gontor Ponorogo East Java Indonesia - Irzal, Muhammad (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study aimed to explore students perception toward their learning style preference in learning Arabic as the main subject in Darussalam Modern Islamic Boarding School as well as analyzing some significant differences among students learning style preference. As a boarding school with huge number of students from different culture and background, it is important to understand students' learning style preference to gain a better approach in teaching and learning among in these heterogeneous students. To achieve this purpose, a stratified sampling was used to choose 344 students from both of male and female main campus were used as the sample of this quantitative research. The collected data was analyzed with each of descriptive, t-test and ANOVA to answer three research questions in this study. The findings of this study showed that audio learning style is the most preferred learning style to the students. It also showed that some items are more preferable by the students. The findings regarding some differences among students with their learning style preference showed the insignificant different of five items explored in this study. Furthermore, this study revealed that audio learning approach is the most preferred approach that needs to be facilitated by teacher in learning Arabic. And since some differences in students' classroom is unpredictable, teachers need to respond to this situation by observing students' preferred ways in learning and making the various approaches to accommodate these differences.